Optimization of Pitfall Trap-Based Practicum to Create Student’s Well-being during the Covid-19 Pandemic - Tabitha Sri Hartati Wulandari; Salma Auliya Yoviska; Ita Rahmawati, Nur; Cacik, Sri (Universitas Pancasakti Tegal, 2022)
The Covid-19 pandemic has impacted all sectors including the education. The government applies online learning to stop the spread of Covid-19 virus. So that, motivation, results, and Student’s Well-being have decreased. Teachers are required to be more creative in choosing learning methods that can create Student’s Well-being. The purpose of this study was to create Student’s Well-being in undergraduate Biology Education by practical activities on insects’s material. The practicum is carried out at home using a Pitfall Trap. This research is a quantitative descriptive study which was conducted using the One-case Study method. The research subjects were 9 student’s class 2020 of undergraduated Biology Education. The data collection was carried out by observation using a student response questionnaire sheet. The results showed that Pitfall Trap-based practicum carried out at home could create Student’s Well-being in undergraduate Biologi Education